Penerapan Tata Kelola Cerdas (Smart Governance) Dalam Mengatasi Covid-19 Di Kota Tangerang Sebagai Kota Cerdas (Smart City) - Nataya, Azlya Salsabila; Kurniawan, Irvan Arif; Prasetyo, Eko (Peneliti.net, 2024)
With the Covid-19 outbreak that hit Tangerang City, it can still make a Smart City (Smart City) with different conditions due to the Covid-19 outbreak. Tangerang City needs to implement Smart Governance which will help Tangerang City become a Smart City during a pandemic. Therefore the City of Tangerang implements Smart Governance in the form of implementing the Large-Scale Social Restrictions (PSBB) policy by implementing a public service application in the form of the Tangerang Live application. The Health Office has also implemented applications in the form of Sirona, Sigacor (Corona Alert), SIDATA, and the Tangerang Live application which is also used for the public to make reports, complaints and suggestions, then how to handle reporting through the application can solve problems, and how quickly officers can come directly to location of cases after someone reported an emergency in the city. In this case, of course, a Standard Operating Procedure (SOP) is needed in implementing the Smart City concept using technology. The method used in this study uses descriptive research methods with a qualitative approach to data collection techniques through interviews and documentation. So this study aims to see how the Government and the Health Service deal with Covid-19 by implementing Smart Governance, especially to reduce the number of Covid-19 cases.